Disulfiram, an aldehyde dehydrogenase inhibitor, works as a potent drug against sepsis and cancer via NETosis, pyroptosis, apoptosis, ferroptosis, and cuproptosis. Issue 3 (1st July 2022) - Nie, Dingrui; Chen, Cunte; Li, Yangqiu; Zeng, Chengwu
Abstract : Regulated cell death (RCD) is essential for maintaining cell homeostasis and preventing diseases. Besides classical apoptosis, several novel nonapoptotic forms of RCD including NETosis, pyroptosis, ferroptosis, and cuproptosis have been reported and are increasingly being implicated in various cancers and inflammation. Disulfiram (DSF), an aldehyde dehydrogenase inhibitor, has been used clinically for decades as an anti-alcoholic drug. New studies have shown that DSF possesses potent anti-inflammatory and anti-cancer effects by regulating these new types of RCD. Here, we summarize the mechanisms and discuss the potential application of DSF in the treatment of cancers and inflammatory diseases.